The Failures of Culture Planning: The National Jubilee as an Object of Political Disagreement - Trilupaitytė, Skaidra (Politologija, 2019)
[full article and abstract in Lithuanian; abstract in English]This article offers an analysis of public critiques and political disagreements regarding the program “Vilnius – European Capital of Culture 2009” and the centennial commemoration of the restored Lithuania, which was celebrated in 2018. The premises of the culture planning paradigm are critically scrutinized, and the confrontations between living culture and strategic planning (unavoidable in political reality) are discussed. The occasions of state or city jubilees somehow make it obligatory for the national community to mention and celebrate the important dates in a “proper” way. But when the actual date approaches, the discussions in the public space reveal the contradictions and a divergence between the different understandings of “culture as display” and civil cultures. The government convenes committees and approves programs. The public figures, media, as well as politicians stress that an upcoming national holiday should be a feast for the people, not for those in power. The requirement for ideological unity is put forward along the political talks regarding the necessity of assigning a special budget for the event. After the routine procedures of political elections (be it national or local), however, the ideas and programs of predecessors are criticized, even ridiculed, and become subject for change. Instances of political disagreements and the ensuing conflict over cultural regulations suggest that a critical cultural policy becomes a useful tool for the analysis of debates in public space. In making cultural policy and culture management decisions, one should be careful of pitfalls in the culture planning model, i.e., along the success stories one should learn from various, not only positive experiences and evaluate the possibilities of failure in culture planning.
Keywords: capital of culture; cultural policy; culture planning